2017
DOI: 10.1007/s00253-017-8355-9
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Rummeliibacillus pycnus arginase with multi-copy insertion of the arg R.pyc cassette into the Bacillus subtilis chromosome

Abstract: A plasmid-less and marker-less strain with multi-copy integration of the arginase gene from Rummeliibacillus pycnus was constructed using Bacillus subtilis 168 as a host. A total of nine copies of the arg cassettes, in which the R. pycnus arginase gene was fused with the strong promoter P43, were inserted into the recipient chromosome. These multiple insertions were completed via step-by-step integrations into designed (2 copies) and random (9 copies) sites, respectively. A strategy for random site integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Several methods are available for multi-copy insertions of the target gene. Among them, integration at two and more different chromosomal sites may be the most stable [ 28 ], so the expression cassette was inserted into both the amyE and the lacA loci to increase the magnitude of expression of the target gene. The vector was first transformed into competent B. subtilis cells and the integration occurred at the amyE locus in the presence of spectinomycin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several methods are available for multi-copy insertions of the target gene. Among them, integration at two and more different chromosomal sites may be the most stable [ 28 ], so the expression cassette was inserted into both the amyE and the lacA loci to increase the magnitude of expression of the target gene. The vector was first transformed into competent B. subtilis cells and the integration occurred at the amyE locus in the presence of spectinomycin.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, nine copies of a arg R.pyc cassette containing the Rummeliibacillus pycnus arginase gene regulated by the strong promoter P43 were inserted into the recipient’s genome. Tests showed that the highest arginase activity (14.5 U/mL) was obtained from flask cultures, and this segregation-stable strain could efficiently hydrolyze l -arginine with a 97.2 % molar yield, suggesting a potential application for the food industry [ 28 ]. A strong promoter was engineered that allowed synthesis of BgaB and sfGFP to levels of 43 % and 30 % of intracellular proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it can convert palm oil mill effluent into terpolymer polyhydroxyalkanoate and biodiesel (3), and it has potential for biomineralization (4). Furthermore, a thermally stable arginase from R. pycnus is used in the production of l -ornithine (5, 6). In this study, we report the draft genome sequence of Rummeliibacillus sp.…”
Section: Announcementmentioning
confidence: 99%